High-risk human papillomavirus enhances the expression of COX-2 VEGF, EGFR, ProEx-C, and TERT proteins in human papillomavirus-related multiphenotypic sinonasal carcinoma through activation of PI3K/Akt, pRb, and TERT signalling pathways - Hanafy, Sabah; Elhasadi, Ibtesami; Alabiad, Mohamed; Refaat, Mohamed; Bakry, Adel; Abdulmageed, Alsayed; Shalaby, Amany; Jaber, Fatima A.; Gobran, Mai Ahmed (Polish Journal of Pathology, 2022)
Human papillomavirus (HPV)-related multiphenotypic sinonasal carcinoma (HMSC) is a new type of sinonasal tumour that frequently drops out of accurate diagnosis. Human papillomavirus related multiphenotypic sinonasal carcinoma was previously known as HPV-related sinonasal carcinoma with adenoid cystic characteristics, and it is connected to high-risk HPV (HR-HPV) strains whose prognosis is unknown. We aim to evaluate PI3K/Akt, pRb, and h telomerase reverse transcriptase (TERT) signalling pathway activation through the expression of proteins cyclooxygenase-2 (COX-2), vascular endothelial growth factor (VEGF), ProEx-C, and TERT and their prognostic and clinicopathological value in HMSC patients. Sections of the 40 paraffin blocks of HMSC were recovered, and all samples were evaluated for the presence of a cocktail of HR-HPV, and the absence of MYB, NFIB, and MYBL1 fusions using fluorescence in situ hybridization; the presence of myoepithelial markers; S100, actin; the presence of squamous differentiation markers; calponin, p40, and p63 using PCR-based assays; and COX-2,VEGF, ProEx-C, and TERT using immunohistochemical staining. All patients were monitored for around 54 months, until death, or the last known surviving data (range 20–60 months). A statistically significant relationship exists between COX-2 expression was significantly related to the old age group, tumour extent, relapse, mortality, and poor DFS; (p = 0.001), (p = 0.01), (p = 0.002), and (p = 0.035), respectively. While VEGF, ProEx-C, and TERT expression with the old age group, tumour extent, lymph node metastasis, advancedstaging, relapse, mortality, poor disease free survival (DFS), and overall survival (p = 0.001). Human papillomavirus-related multiphenotypic sinonasal carcinoma is a unique sinonasal neoplasm with a strong link to HR-HPV strains. Expression of COX-2, VEGF, EGFR, ProEx-C, TERT was linked to poor prognosis, survival, and aggressive malignant behaviours such as proliferation, local recurrence, and lymph node metastasis, making them novel beneficial biomarkers and targeted therapies for HMSC patients.